The demise of multidrug-resistant HIV-1: the national time trend in Portugal - Vercauteren, Jurgen (Oxford University Press, 2013)
OBJECTIVES: Despite a decreasing mortality and morbidity in treated HIV-1 patients, highly active antiretroviral treatment (HAART) can still fail due to the development of drug resistance. Especially, multidrug-resistant viruses pose a threat to efficient therapy. We studied the changing prevalence of multidrug resistance (MDR) over time in a cohort of HIV-1-infected patients in Portugal. PATIENTS AND METHODS: We used data of 8065 HIV-1-infected patients followed from July 2001 up to April 2012 in 22 hospitals located in Portugal. MDR at a specific date of sampling was defined as no more than one fully active drug (excluding integrase and entry inhibitors) at that time authorized by the Portuguese National Authority of Medicines and Health Products (INFARMED), as interpreted with the Rega algorithm version 8.0.2. A generalized linear mixed model was used to study the time trend of the prevalence of MDR. RESULTS: We observed a statistically significant decrease in the prevalence of MDR over the last decade, from 6.9% (95% CI: 5.7–8.4) in 2001–03, 6.0% (95% CI: 4.9–7.2) in 2003–05, 3.7% (95% CI: 2.8–4.8) in 2005–07 and 1.6% (95% CI: 1.1–2.2) in 2007–09 down to 0.6% (95% CI: 0.3–0.9) in 2009–12 [OR = 0.80 (95% CI: 0.75–0.86); P < 0.001]. In July 2011 the last new case of MDR was seen. CONCLUSIONS: The prevalence of multidrug-resistant HIV-1 is decreasing over time in Portugal, reflecting the increasing efficiency of HAART and the availability of new drugs. Therefore, in designing a new drug, safety and practical aspects, e.g. less toxicity and ease of use, may need more attention than focusing mainly on efficacy against resistant strains.